Sistem Pengambilan Keputusan Untuk Pengolahan Data Siswa Penerima Bantuan Belajar Komputer Gratis - Anggi Sofiani; Marnis Nasution; Irmayanti Irmayanti (Jurnal Informatika, 2024)
Students play an important role in learning computers, especially in the process of education and learning. According to Law No. 14 of 2005 article 51 paragraph 1 item b states that students are entitled to receive awards for their performance during computer Learning . On the other hand, information technology continues to develop rapidly, one of the developments in information technology is the emergence of Decision Support Systems. Decision support system is a system that helps decision makers in making a decision.There are many methods or algorithms that can be used in decision support systems, including Weighted Product (WP), TOPSIS, Simple Addictive Weighting (SAW), Analytical Hierarchy Process (AHP) methods and others. Analytical Hierarchy Process (AHP) method is one method that has been widely used in Decision Support Systems. This method has the ability to measure the degree of consistency of the decisions to be made. One of the consistency calculations performed in the AHP method is the calculation of the consistency ratio, which in this calculation is done using the value of the random index (IR). Over time, many researchers have conducted research on the value of the Analytical Hierarchy Process random index, so there are many new random index values in addition to the AHP random index found by students.